PENGARUH PELAKSANAAN PEMASARAN TERHADAP VOLUME PENJUALAN INDUSTRI KECIL BATU BATA KULIM PEKANBARU - Septi Adi Sudirga; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Marketing represent one of the fundamental activity conducted by a company or industrial in effort to market his/its yield up the ghost, expanding and having the advantage of operasinya.Berhasil or do not it him the attainment tujauan very depended to membership in the field of production, finance, ability and promotion combine the effort the marketing in order to the ambulatory brick industry at ease.This research was conducted atHospital Syafira Pekanbaru.Lokated at JendralSudirman street, No. 134, Pekanbaru. The purpose of this Research was conductedto determinethe effect of the implementation of the marketing strategy of the interst of patient in Hospitals of Syafira Pekanbaru.As for location of this research is at industry of brick addressing in Subdistrict of Great Tenayan, Kulim, Pekanbaru representing distributor of product marketing brickIn this research is methodologies used by is quantitative and descriptive with program SPSS, where sampel used by that is Population in this research in entire/all unit of[is effort industry of brick which is gone the round of in Subdistrict of Great Tenayan, Kulim, Pekanbaru with amount 60 unit of[is effort. To determine sampel use census. Technics of data collecting of through interview, observation and kuesioner.From result analyse data covering validity test, reabilitas, and linear regresi modestly, execution of marketing in this research cover product, price, place, promotion. Each owning indicator which each other be interconnected and have an effect on positive to sale volume.Keyword: Marketing, sale volume